PERCEPTUAL SIDE OF INTERPERSONAL RELATIONS IN COMMUNICATION - Ruziev Nodirbek Ikromovich (Western European Studies, 2024)
Communication is a major component of the human second signaling system. In interpersonal communication, in addition to expressing your opinion, expressing your needs, expressing your feelings, you can enter into a dialogue by listening to the opinion of another person, listening to your wishes, expressing sympathy, and in the process of communication - communicative (transfer of information), interactive (joint action) and perceptual (joint) perception. Below we will look at the mechanisms that influence a person’s perception of a person in the process of communication.
Keywords: perception; identification; reflection; stereotyping